2020
DOI: 10.3390/ma13235313
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Tensile Properties and Energy Dissipation of High-Strength Concrete after Exposure to Elevated Temperatures

Abstract: In view of the devastating outcomes of fires and explosions, it is imperative to research the dynamic responses of concrete structures at high temperatures. For this purpose, the effects of the strain rate and high temperatures on the dynamic tension behavior and energy characteristics of high-strength concrete were investigated in this paper. Dynamic tests were conducted on high-strength concrete after exposure to the temperatures of 200, 400, and 600 °C by utilizing a 74 mm diameter split Hopkinson pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“… where is the static strength and is the dynamic maximal compression stress. When analyzing the dynamic properties of concrete by an SHPB device, the increase rate of the dynamic strength is often evaluated by the relationship between DIF and the logarithm of strain rate [ 29 , 30 , 31 , 32 , 34 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… where is the static strength and is the dynamic maximal compression stress. When analyzing the dynamic properties of concrete by an SHPB device, the increase rate of the dynamic strength is often evaluated by the relationship between DIF and the logarithm of strain rate [ 29 , 30 , 31 , 32 , 34 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The strain rate sensitivity is proven to be one of the significant properties of concrete [28][29][30][31][32][33]. In recent years, some researchers found that severe environmental factors would seriously deteriorate the dynamic performance of concrete [34][35][36][37]. Unfortunately, few studies focus on the influence of aging effects on the dynamic behaviors of EPC.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature [ 30 ], the measured incident waves with the peak value of 33.15 MPa, 56.37 MPa, 80.54 MPa and 112.74 MPa were applied on the end face of the incident bar, and the rising stage was 170 µs, the peak duration was 198 µs, and the decrease time was 208 µs. The axial strain history curves of the elements at the center of the SHPB incident and transmission bars are extracted respectively, and the compressive strain rates and strains of the specimens under different incident waves can be obtained by using Equations (1) and (2) [ 12 ]. From the results of photo-elastic experiments, Gomez et al [ 42 ] concluded that when a specimen experienced stress equilibrium, its dynamic stress distribution is similar to that of splitting stress under static load.…”
Section: Simulation Of Dynamic Splittingmentioning
confidence: 99%
“…It can measure the stress-strain curves of materials at high strain rates (10 2 –10 4 s −1 ), and is also the most basic experimental techniques to study the dynamic failure process of concrete materials. Nowadays, many scholars have used Split Hopkinson Pressure Bar (SHPB) device to conduct experimental research on dynamic splitting of concrete, and achieved some relevant results [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical composition and geometric characteristics of cement and silica fume[31]. Chemical composition of tap water (mg/L).…”
mentioning
confidence: 99%